Optimalisasi Metode Gerak serta Lagu untuk Meningkatkan Kecerdasan Peserta Didik - Rif'atin Rif'atin (AS-SABIQUN, 2019)
This research is based on the lack of variations in songs used by teachers in learning for early childhood. The purpose of this study is to develop motion and song activities that can be used as a choice of activities that can be done to improve children's intelligence and to find out whether motion activities and songs developed by researchers are effective to improve children's intelligence. This type of research is descriptive qualitative research, in order to obtain data in this study the authors use classroom action research methods through observation methods, capacity assessment formats and documentation. From the data analysis it is known that the intelligence of children after being given an experiment through motion activity and better than the intelligence of children before being given experiments through motion and song activity. In general, motion and song can develop children's kinesthetic intelligence, through body movements such as by bending with rotating the body, it can be concluded that movement and song activity is effective to improve children's intelligence.